Electrode potential-modulated cleavage of surface-confined DNA by hydroxyl radicals detected by an electrochemical biosensor - Fojta, M; Kubicárová, T; Palecek, E (Biosensors & bioelectronics, 2000)
Damage to DNA frequently involves interruption of DNA sugar-phosphate strands (strand breaks, sb). Under aerobic conditions, transition metal ions cause DNA damage through production of reactive oxygen species (frequently via Fenton-type reactions). Formation of sb in covalently closed supercoiled (sc) DNA can be detected using an electrochemical biosensor based on a scDNA-modified mercury electrode. By controlling the potential of the electrode, this technique can be employed in studies of redox reactions involved in formation of DNA strand breaks, and to detect species involved in these reactions. ScDNA anchored at HMDE was cleaved by catalytic amounts of iron/EDTA ions in the absence of chemical reductants when appropriate electrode potential (sufficiently negative to reduce [Fe(EDTA)]- to [Fe(EDTA)]2-) was applied. The process required oxygen or hydrogen peroxide. The extent of DNA damage increased with the shift of the electrode potential to negative values, displaying a sharp inflection point matching the potential of [Fe(EDTA)]2-/[Fe(EDTA)]- redox pair. In the absence of transition metal ions, significant DNA damage was observed at potentials sufficiently negative for reduction of dioxygen at the mercury electrode. This observation suggests cleavage of the surface-attached scDNA by radical intermediates of oxygen reduction at HMDE.
Keywords: železo; Electrodes; Electrochemistry; Iron; elektrochemie; Biosensing Techniques; oxidace-redukce; elektrody; biosenzitivní techniky; Edetic Acid; superhelikální DNA; hydroxylový radikál; peroxid vodíku; Hydroxyl Radical; Oxidation-Reduction; poškození DNA; DNA Damage; EDTA; DNA, Superhelical; Hydrogen Peroxide